The quick six fix : 100 no-fuss, full flavor recipes : 6 ingredients, 6 minutes prep, 6 minutes clean-up - O'Keeffe, Stuart; Squires, Kathleen (William Morrow, an imprint of HarperCollinsPublishers, 2016)
"Save time and simplify with 100 fabulous quick-and-easy recipes--using 6 ingredients, 6 minutes of prep, and 6 minutes of clean up--from celebrity chef Stuart OKeeffe,"--Amazon.com.